2012
DOI: 10.1136/flgastro-2012-100200
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease in Asians in a single centre in southern Derbyshire

Abstract: Background Coeliac disease affects adult Asians from north India, Pakistan and Bangladesh in the UK but how commonly this occurs is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…36 A full epidemiological analysis of Asians has not been undertaken in this new study because the ONS has not yet published population estimates by ethnicity beyond 2010. However, the data collected are informative.…”
Section: Discussionmentioning
confidence: 99%
“…36 A full epidemiological analysis of Asians has not been undertaken in this new study because the ONS has not yet published population estimates by ethnicity beyond 2010. However, the data collected are informative.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study regarding the difference in rates of dietary adherence between Asian and Caucasian patients with coeliac disease corroborate the results of the study by Holmes et al . , although they demonstrate a greater difference in the rates of dietary adherence between the two populations. Our results differ from the results of the study by Muhammad et al .…”
Section: Discussionmentioning
confidence: 74%
“…The results of the present study are being reported in the context of recent studies on dietary adherence in South Asian patients with coeliac disease, including studies by Butterworth et al . , Holmes and Moor and Muhammad et al . .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations